2018
DOI: 10.1523/jneurosci.1314-18.2018
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Beta Bursts in the Subthalamic Nucleus Predicts Motor Performance

Abstract: Considerable evidence suggests a role of beta-band oscillations in voluntary movements. However, most of the studies linking beta power to motor performance are based on data averaged across trials that ignore the fast dynamics of oscillatory activity and trial-to-trial variations in motor responses. Recently, emphasis has shifted from the functional implications of the mean beta power to the presence and nature of episodic bursts of beta activity. Here we test the hypothesis that beta bursts, though short in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
163
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 134 publications
(170 citation statements)
references
References 50 publications
6
163
1
Order By: Relevance
“…This growing body of evidence supports the hypothesis that longer duration beta bursts in subcortical structures, equating to longer periods of beta oscillations and synchrony, represent pathological or impaired sensorimotor processing in Parkinson's disease (Anidi et al, 2018;Cagnan et al, 2019;Deffains et al, 2018;Lofredi et al, 2019b;Tinkhauser et al, 2018Tinkhauser et al, , 2017aTinkhauser et al, , 2017b and that one mechanism of STN DBS is to remove pathological sensorimotor network processing, while leaving intact normal physiological processing (Anidi et al, 2018;Holt et al, 2019;Tinkhauser et al, 2017a;Torrecillos et al, 2018). The discovery that averaged beta band power was attenuated during increasing intensities of DBS led to its successful use as the control variable in closed loop DBS studies Eusebio et al, 2011;Little et al, 2016aLittle et al, , 2016bLittle et al, , 2013Piña-Fuentes et al, 2019Rosa et al, 2017Rosa et al, , 2015Syrkin-Nikolau et al, 2017;Velisar et al, 2019;Whitmer et al, 2012).…”
Section: Beta Burst Duration As a Biomarker Of The Efficacy Of Therapsupporting
confidence: 53%
See 2 more Smart Citations
“…This growing body of evidence supports the hypothesis that longer duration beta bursts in subcortical structures, equating to longer periods of beta oscillations and synchrony, represent pathological or impaired sensorimotor processing in Parkinson's disease (Anidi et al, 2018;Cagnan et al, 2019;Deffains et al, 2018;Lofredi et al, 2019b;Tinkhauser et al, 2018Tinkhauser et al, , 2017aTinkhauser et al, , 2017b and that one mechanism of STN DBS is to remove pathological sensorimotor network processing, while leaving intact normal physiological processing (Anidi et al, 2018;Holt et al, 2019;Tinkhauser et al, 2017a;Torrecillos et al, 2018). The discovery that averaged beta band power was attenuated during increasing intensities of DBS led to its successful use as the control variable in closed loop DBS studies Eusebio et al, 2011;Little et al, 2016aLittle et al, , 2016bLittle et al, , 2013Piña-Fuentes et al, 2019Rosa et al, 2017Rosa et al, , 2015Syrkin-Nikolau et al, 2017;Velisar et al, 2019;Whitmer et al, 2012).…”
Section: Beta Burst Duration As a Biomarker Of The Efficacy Of Therapsupporting
confidence: 53%
“…Aspects of the signal were only included in the burst analysis if and when instantaneous power rose above a threshold of the power of the LFP signal within that band or within the overall beta band, with or without a temporal threshold (e.g. power elevated for greater than a defined number of oscillatory cycles), Deffains et al, 2018;Feingold et al, 2015;Lofredi et al, 2019b;Meidahl et al, 2019;Tinkhauser et al, 2017aTinkhauser et al, , 2017bTinkhauser et al, , 2018Torrecillos et al, 2018). Most publications have followed the method described by Tinkhauser et al, who defined a burst when power exceeded a threshold of 75% of the power of the rectified smoothed signal.…”
Section: Measurements Of the Dynamics Of Pathological Beta Band Neuramentioning
confidence: 99%
See 1 more Smart Citation
“…1a), 2. burst-rate-increase will lead to global (averaged) power increase, and 3. burst occurrences can be predicted based on behavioural readouts.As a test-bed for these hypotheses, we chose the rat motor cortex and focused on LFP bursts of betawaves (15-30 Hz), which have been documented in humans, monkeys, and mice. These short bursts (<150 ms) have been correlated with memory, movement and perception [4][5][6]8,9 , and reported to be correlated with behaviour up to 300 ms relative to the burst occurrence 8 .…”
mentioning
confidence: 90%
“…Many studies have shown that beta band activity is enhanced during tonic contractions and diminished during dynamic voluntary movement (Sanes & Donoghue 1993, Baker et al 1997, Kilner et al 1999, Riddle & Baker 2006, Baker 2007, Klostermann et al 2007, Chakarov et al 2009, and can be observed at different levels of the central nervous system including motor cortex, basal ganglia and motor units in the periphery (Baker 2007, Brown 2007. Recently it was shown that movement-related modulations of beta oscillatory activity occur in brief bursts rather than as an ongoing rhythm (Feingold et al 2015, Torrecillos et al 2018. Beta band activity is thought to reflect a mechanism involved in maintaining the current sensorimotor state (Baker 2007, Engel & Fries 2010, van Wijk et al 2012).…”
Section: Physiology Of Low Beta Oscillationsmentioning
confidence: 99%